2021
DOI: 10.1155/2021/3707058
|View full text |Cite
|
Sign up to set email alerts
|

Saireito Improves Lymphatic Function and Prevents UVB-Induced Acute Inflammation and Photodamage in HR-1 Hairless Mice

Abstract: A single high-dose ultraviolet B (UVB) exposure on the skin induces acute inflammatory responses, such as an increase in proinflammatory cytokines (e.g., IL-6 and IL-1β), hyperpermeability and dilation of blood and lymphatic vessels, and infiltration of inflammatory cells. These responses result in different cutaneous disorders characterized by erythema, epidermal hyperplasia, edema formation, and extracellular matrix degradation. Saireito extract (SRT), a traditional Chinese medicine, has been used to treat v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
1
1
0
Order By: Relevance
“…Among the markers, the baicalin (major compound of S. baicalensis) content was highest at 16.63-16.86 mg/g. Our results show that this is similar to the results of previous studies reporting the qualitative analysis of SRT [14,15].…”
Section: Quantification Of the 12 Marker Analytes In Srt Samplessupporting
confidence: 92%
“…Among the markers, the baicalin (major compound of S. baicalensis) content was highest at 16.63-16.86 mg/g. Our results show that this is similar to the results of previous studies reporting the qualitative analysis of SRT [14,15].…”
Section: Quantification Of the 12 Marker Analytes In Srt Samplessupporting
confidence: 92%
“…Furthermore, steroids induce fibrosis through connective tissue growth factor (CTGF), a profibrotic cytokine [8]. On the other hand, it was reported that saireito involves suppression of the upregulation of the proinflammatory cytokines IL‐1 β and IL‐6, and improvement of the lymphatic function in the early stage of inflammation, using a mouse model irradiated with ultraviolet B [9].…”
Section: Discussionmentioning
confidence: 99%